Cell-wall chemical-composition analysis of a Saccharum spp. progeny for increased bagasse digestibility - Garcia, José María (2019)
XXX Congress of the ISSCT (International Society of Sugar Cane Technologists), Tucumán, from 31 August to 8 September 2019